Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1007/bf01076410
|View full text |Cite
|
Sign up to set email alerts
|

Strain-differentiated circadian and ultradian rhythms in locomotor activity of the laboratory rat

Abstract: Spontaneous locomotor activity (LA) was recorded in five inbred strains of laboratory rats (ACI/ZtmKEY WORDS: circadian and ultradian rhythms; strain differences; locomotor activity; laboratory rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
29
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 20 publications
(13 reference statements)
7
29
0
Order By: Relevance
“…LEW rats showed a multimodal activity pattern with two rather short activity bouts about 3-5 hours apart from each other. Previous studies have shown a similar pattern in the daily rhythms o f overall activity as measured with an Animex-like svstem (7 ). body temperature and heart rate (6).…”
Section: Discuss Io!'-supporting
confidence: 59%
“…LEW rats showed a multimodal activity pattern with two rather short activity bouts about 3-5 hours apart from each other. Previous studies have shown a similar pattern in the daily rhythms o f overall activity as measured with an Animex-like svstem (7 ). body temperature and heart rate (6).…”
Section: Discuss Io!'-supporting
confidence: 59%
“…The origin of similar temporal variations on a smaUer time scale, caUed ultradian or short-term rhythms, remains unclear [11]. Ultradian rhythms in locomotor activity are known to exist in laboratory rats [8, 9, 2~30, 49], however, attracting much less attention than circadian rhythms.A recent study of LEW/Ztm rats has shown that ultradian rhythms of 4 and 4.8 hr periods are geneticaUy fixed in this Estradiol Testosterone inbred strain (9]. The persistence of these ultradian rhythms foUowing the disruption of circadian organization under continuous light supported the assumption that the activity rhythms of this strain are caused by an independent ultradian oscillator [9].…”
mentioning
confidence: 93%
“…Measurements performed on rats of the BH and LEW strains under continuous light conditions confirmed the assumption of an independent ultradian oscillator which causes activity rhythms in the LEW and BH strains [7]. Other authors [13), however, suggest that ultradian rhythmicity reflects the activity of several circadian oscillators coupled to one another in various phase relations (i.e.…”
Section: Sex Differences In the Daily Pattern Of Locomotor Activity Imentioning
confidence: 64%
“…Ultradian rhythms, which have been found to be genetically fixed in two inbred strains of rats [7], are also sex-specific. They w~re observed in male animals of these strains.…”
Section: Sex Differences In the Daily Pattern Of Locomotor Activity Imentioning
confidence: 97%
See 1 more Smart Citation